Development and validation a methodology model for traditional Chinese medicine good practice recommendation: an exploratory sequential mixed methods study - Li, Su; Zhang, Luan; Wang, Yangyang; Xie, Runsheng; Chen, Wenjia; Lee, Myeong Soo; Amer, Yasser Sami; Sharifan, Amin; Hussein, Heba; Li, Hui (Frontiers in Pharmacology, 2025)
BackgroundTo develop a rational and standardized traditional Chinese medicine (TCM) good practice recommendation (GPR) methodology model that guides the formulation of recommendations grounded in clinical experience.MethodsWe adopted an exploratory sequential mixed-method to develop a methodology model by coding systematically collected literature on methodology and TCM guidelines related to TCM GPR using a best-fit framework synthesis. Then based on real-world data (published TCM guidelines), saturation tests, structural rationality validation, and discriminability tests were conducted to validate methodology model.ResultsA total of 35 methodological literature and 190 TCM guidelines were included. A TCM GPR methodology model was developed, including 3 themes, 10 sub-themes, and the relationships between themes and subthemes. The information of TCM GPR methodology model achieved data saturation. The fit indices were within the acceptable range, and were able to distinguish the overall differences between guidelines from different literature sources, development organizations, guideline types, discipline categories, and funding categories.ConclusionThe study developed a TCM GPR methodology model which describes the definition of a TCM GPR, how to formulate it, and how to report it. The methodology modeldemonstrates good fit, discriminability, and data saturation. It can standardize the specific formulation of TCM GPRs, facilitate the scientific and rational formation of TCM GPRs, and provide theoretical and methodological guidance for the formation of TCM GPRs.